Analisis Kualitas Peluru MU-5 TJ Pindad Dari Pengaruh Suhu Dibawah 0 °C Dengan Pengujian Fungsi dan Kadar Abu - Santosa, Tata (Akademi Angkatan Udara, 2022)
A munition is an object that has a certain shape and ballistic properties that can be filled with explosives and can be fired with weapons with the intention of to damage or destroy a certain target. The simplest munition consist of a projectile, a shell and an explosive which acts as a propellant. In a military operation, it is very possible for munitions to be exposed to cold temperatures even below 0°C, for example in high mountainous terrain. Therefore, it will be investigated the effect of cold temperature on the quality of the munition in terms of the function of the munition and the ash content of the propellant of the munition. The munition used in this project is the MU-5 TJ 5.56 mm caliber munition produced by PT. Pindad in 2015 at the Yogyakarta Air Force Academy. The MU-5 TJ munition will be analyzed the function of munition and ash content of the propellant of munition after cooling treatment at temperatures below 0°C by storing the munitions in the freezer with variations in cooling time of 3 and 5 days. The ash content test was carried out on the propellant of the munition by heating at a temperature of 700 °C for 1 hour. The function test was carried out by firing 10 munitions with SS1-V1 weapons and then calculating the percentage of exploding munitions. Functional and ash content tests were also carried out on uncooled munitions and this was considered a 0 day cooling time for comparison. From the results of the analysis of the data obtained, it can be concluded that the cooling treatment at temperatures below 0 °C for 5 days on the MU-5 TJ munition affects the quality of the munition in terms of ash content and munition function. Ash content increased significantly from 0.596% (0 days cooling time) to 0.925% (5 days cooling time) and bullet function decreased from 100% (0 and 3 days cooling time) to 82% (5 days cooling time). The MU-5 TJ munition which received cooling treatment at temperatures below 0 °C for 5 days was not suitable for use according to PTU standards number 121 Repair I Year 2000 and T.O. 11A-1-10.